Pierre’o Bourdieu literatūros sociologija - Jakonytė, Loreta (Literatūra, 2015)
The paper deals with the sociology of literature of Pierre Bourdieu, one of the most influential figures in contemporary sociology of art. Initially, Bourdieu intended to overcome dichotomy of formalistic and contextual approaches, to transcend both the subjectivism and objectivism and to situate culture within broader social context and power relations. The sociologist suggested a systematic approach to literary practise and elaborated a theory of fields, the key terms of which are field, habitus, economic, social, cultural and symbolic capital, struggles, stake, structural homology, positions, dispositions, domination, strategy etc. The specificity of the literary field is defined mostly by the concepts of relative autonomy and “reversed” economy. Bourdieu examines the social positions of individuals and institutions involved in making cultural products (writers, publishers, critics, readers etc.), the social conditions, circulation and consumption of literary works. In this conceptual framework, literary text gains a specific status as the independent object of analysis (even such literary features as genre, narrative devices, types of characters etc. have special social meaning and function), what distinguishes Bourdieu from many his predecessors. His practical researches bring together various methods and combine empirical analysis with a strong theoretical frame. Numerous contemporary projects of sociology of culture are based on Bourdieu’s ideas. Some issues, however, have been brought for discussion, especially the universality of the notions and the concept of autonomy. Bourdieu constructed a powerful, highly theoretically structured model for interpretation of literature. It integrates every element of culture and provides tools for revealing their complex dialectical relations. Bourdieu’s sociology of literature might be a beneficial mode of analysis for Lithuanian literary scholars.